LOGIC OR PUBLIC POLICY: SHOULD “CONFIRMATORY STATEMENTS” BE ACTIONABLE UNDER RULE 10b-5? - Keegan, Sean (Journal of Law and Commerce, 2013)
LOGIC OR PUBLIC POLICY: SHOULD “CONFIRMATORY STATEMENTS” BE ACTIONABLE UNDER RULE 10b-5?